Alternative treatment of bovine mastitis - Mimoune, Nora (Array, 2021)
The treatment of mastitis is based mainly on the use of antibiotics. However, in recent times, an increase in resistance phenomena and the presence of residues in milk and their derivatives has been reported. Few studies have focused on the treatment of mastitis by homeopathy elsewhere or in Algeria. The objective of this current study aimed to clarify in particular the interest of homeopathy in the treatment of mastitis. The study was carried out on two dairy farms on a total of 14 cows located in Laghouat region (southern Algeria). Before the start of the experiment, a tolerance test was performed on two cull cows free from any apparent infection (except mastitis). Local and general reactions were noted at specific times. A total of 31 mammary quarters received 4 intramammary injections of a homeopathic preparation containing several natural products every 12h over 48h. A clinical examination and an analysis of the milk samples on D0, D7 and D14 were performed on all cows and the conclusion was made on the day 14. Data showed a very good tolerance to the homeopathic preparation and a 75% cure rate of the clinical mastitis. An improvement with a decrease in CMT score was also noted. In addition, healing rates of 51.85% for subclinical mastitis on D7 and 59.29% on D14 were also reported. Ultimately, homeopathy could, in some cases, represent an alternative to antibiotic therapy and bring an advantage to breeders. Further investigations should be performed in the future.